Hubungan Pengetahuan, Sikap dan Perilaku Orang Tua terhadap Pemberian Vaksin Merdeka Anak - Rosani Naim; Ekawati Saputri (LPPM Hang Tuah Pekanbaru, 2023)
Currently, the government's target is to give COVID-19 vaccinations to children aged 6-11 years starting on December 14, 2021, with a target number of vaccinations reaching 26.5 million children. Giving COVID-19 vaccination to children 2 times with an interval of at least 28 days using the Bio Farma COVID-19 vaccine and/or Coronavac. Vaccination in children has been given previously, namely in children aged 12-17 years. Objective: To analyze the relationship of knowledge, attitudes, and behavior of parents to the provision of independent vaccines for children. Methods: Analytical description research with a cross-sectional study approach. The sampling technique used purposive sampling technique with a total sample of 171 people. Results: There is no relationship between parental knowledge (p-value = 0.282) and parents' attitude (p-value = 0.459) toward the administration of the child's independent vaccine. There is a relationship between the behavior of parents (p-value = 0.000) on the provision of independent vaccines for children. Conclusion: Parents' knowledge and attitudes have no effect on interest in vaccinating children because parents believe that the COVID-19 vaccine is very important to prevent children from being exposed to serious risks due to COVID-19. Information about the COVID-19 vaccine is also very important for parents to reduce worries about side effects and vaccine safety. Therefore, the government, doctors, and nurses must always disseminate the COVID-19 vaccine to children.